The Influence of Price, Promotion and Location on Consumer Purchase Decisions on Regen Perfume in Pringsewu - Wahyuni, Sri; Patmarina, Hepiana (The Eastasouth Management and Business, 2025)
This research aims to analyze the influence of price, promotion and location on consumer purchasing decisions for Regen Parfum products in Pringsewu. The research method used is quantitative with a survey approach. Data was collected through a questionnaire distributed to Regen Parfum consumers as respondents. The data analysis technique uses multiple linear regression to determine the extent to which each independent variable (price, promotion and location) contributes to purchasing decisions. The research results show that these three variables simultaneously have a significant influence on purchasing decisions. Partially, price has a significant positive influence because consumers tend to consider the suitability of price to product quality. Promotions also have a significant effect because they provide additional attraction for consumers to make purchases. Location, as the third variable, shows a significant influence because ease of access and convenience of store locations influence consumer decisions. These findings provide implications for Regen Perfum management to continue optimizing price, promotion and location strategies to increase consumer satisfaction and loyalty.